Researching Mahr in Germany: A Multidisciplinary Approach - Günther, Ursula; Herzog, Martin; Müssig, Stephanie (Review of Middle East Studies, 2015)
This article considers the legal institution of mahr in Islamic family law from three research perspectives in order to provide insights into the phenomenon's complexity, particularly with regard to current legal practices. In particular, emphasis is placed both on countries where family law is shaped by Islamic traditions (e.g., Morocco) and on countries whose legal traditions do not have a mahr counterpart (e.g., Germany). First, the social and economic function of dower will be described. As a special form of property transfer, mahr will be analyzed in its historical and present shape in theory and practice. Second, the legal conceptualization of mahr in the German legal context will be discussed. The example of Morocco serves to illustrate the changes with regard to mahr because of the process of incorporation of Islamic legal concepts into a national statutory law system. Given the Muslim diaspora, these insights are important contributions to the legal intepretation of mahr in a transnational context.<br
Keywords: mahr; family law; property transfer; marriage; Muslim diaspora; Islam in Germany; legal practices; transnational contexts of family law; mahr; family law; property transfer; marriage; Muslim diaspora; Islam in Germany; legal practices; transnational contexts of family law